The role of land compulsory purchase in engineering and transport infrastructure development - Petrakovska, Olga; Mykhalova, Mariia (KNUCA, 2015)
This paper deals the consideration of the consequences of unjustified decision making on the land development with the application of land compulsory purchase for the engineering and transport infrastructure construction. In the article are considered the approaches to determine the efficiency of land development from the standpoint of needs of population life support and industry complex as well as investment interests.
РОЛЬ ПРИНУДИТЕЛЬНОГО ИЗЪЯТИЯ ЗЕМЕЛЬ ПРИ СТРОИТЕЛЬСТВЕ ОБЪЕКТОВ ИНЖЕНЕРНОЙ И ТРАНСПОРТНОЙ ИНФРАСТРУКТУРЫ
Keywords: social efficiency; economic efficiency; transport and engineering infrastructure; land development; land compulsory purchase; социальная эффективность; экономическая эффективность; объекты инженерно-транспортной инфраструктуры; развитие территорий; принудительное изъятие